2001
DOI: 10.2310/6650.2001.33721
|View full text |Cite
|
Sign up to set email alerts
|

Heme Oxygenase-1 Protects Pancreatic β Cells from Apoptosis Caused by Various Stimuli

Abstract: Profound cell stress that occurs in islets after transplantation, as well as at the onset of diabetes, results in beta-cell loss through apoptosis. Protection of beta cells by HO-1 improves their survival in vitro after various proapoptotic stimuli, suggesting that HO-1 suppresses one or several signaling pathways leading to apoptosis. We hypothesize that our in vitro findings can be extrapolated to the in vivo situation, and we propose that expression of HO-1 in islets may illuminate a valuable new approach t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(56 citation statements)
references
References 50 publications
3
52
0
1
Order By: Relevance
“…Besides, HO-1 also contributes to cytoprotection by reducing apoptosis. Tobiasch et al demonstrated that CoPPinduced βTC3 cells (an insulinoma cell line) with high HO-1 levels were able to counteract the apoptosis of beta cells caused by various stimuli through activation of the p38 mitogen-activated protein kinase pathway [40]. Our TUNEL assay data apparently support those findings.…”
Section: Discussionsupporting
confidence: 84%
“…Besides, HO-1 also contributes to cytoprotection by reducing apoptosis. Tobiasch et al demonstrated that CoPPinduced βTC3 cells (an insulinoma cell line) with high HO-1 levels were able to counteract the apoptosis of beta cells caused by various stimuli through activation of the p38 mitogen-activated protein kinase pathway [40]. Our TUNEL assay data apparently support those findings.…”
Section: Discussionsupporting
confidence: 84%
“…Among the genes induced by IL-1β and supraphysiological glucose concentrations, the transcription factor c-Myc stimulates apoptosis more than proliferation in rodent beta cells [21][22][23], whereas the antioxidant enzyme haeme-oxygenase 1 (HO1) improves beta cell survival under various stressful conditions [17,[24][25][26]. In vitro, overnight culture of rat islets in the presence of 30 mmol/l glucose (G30) instead of 10 mmol/l glucose (G10) markedly stimulated expression of HO1 and c-Myc at the mRNA and protein levels in a Ca 2+ -and cyclic AMP-dependent manner without affecting c-Myc or HO1 mRNA stability [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…HO-1 upregulation was induced reproducibly with protoporphyrins and was correlated with protection from apoptosis induced in vitro with proinflammatory cytokines or Fas engagement. Furthermore, in vivo, HO-1 upregulation resulted in improved islet function in a model of marginal mass islet transplantation in rodents (Pileggi et al, 2001;Tobiasch et al, 2001).…”
Section: Scavenging-free Radicalsmentioning
confidence: 99%